Gender inequality in public administration. Analysis of the Argentine case between 2009 and 2023 - Castellani, Ana (Revista del CLAD Reforma y Democracia, 2025)
The gender gap in management positions and certain areas of management is a phenomenon that persists in public administrations despite recent progress in women’s participation in various workplaces. This situation poses a challenge to the institutional quality of democracies as the State fails to build bureaucracies representative of the society it governs. The objective of this article is to analyze, in Argentina, the evolution of the gender gap in access to senior public management positions between 2009 and 2023 (what is known as vertical segregation or “glass ceiling”) and to complement this analysis with an analysis of gender gaps by management area (horizontal segregation or “glass walls”) for 2023. It also explores the hypotheses that allow us to understand this evolution based on the public policies implemented during the period. The results obtained will allow us to infer in which types of positions the ceiling specifically begins to operate, which areas of management are most feminized and which are most masculinized, and whether these characteristics are linked to the type of position held, thus establishing relationships between the two types of segregation (vertical and horizontal).